Analisis Optimalisasi Produk Pada Sofie Localfood Di Kota Palu - Fathur Rahman; Asngadi Asngadi; Syamsuddin Syamsuddin; Anisah Anisah (Journal Economic Excellence Ibnu Sina, 2024)
The problem that occurs is optimizing products at Sofie Localfood in Palu City to increase production and income. This research uses quantitative descriptive methods, with primary data and secondary data. The data collection techniques used were observation, interviews and documentation. The data analysis used is linear programming using the simplex method. The results of this research show that product optimization analysis at Sofie Localfood in Palu City can provide significant results for developing the local economy and strengthening regional cultural identity. This research highlights the importance of analyzing the optimization of Sofie localfood products in Palu City in the context of local economic development and regional cultural preservation. By using the simplex method, Sofie localfood producers can identify more efficient production strategies in optimizing the company's products.